2017
DOI: 10.3389/fpls.2017.02112
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Marker Alleles for Panicle Exsertion Length in Rice (Oryza sativa L.) Mined by Association Mapping and the RSTEP-LRT Method

Abstract: The panicle exsertion length (PEL) in rice (Oryza sativa L.) is an important trait for hybrid seed production. We investigated the PEL in a chromosome segment substitution line (CSSL) population consisting of 66 lines and a natural population composed of 540 varieties. In the CSSL population, a total of seven QTLs for PEL were detected across two environments. The percentage of phenotypic variance explained (PVE) ranged from 10.22 to 50.18%, and the additive effect ranged from −1.77 to 6.47 cm. Among the seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…This indicates that this favorable allele could be used to increase the length of the 1IN in breeding programs and, consequently, would be of great value for panicle exertion enhancement. It is supported by previous studies that the elongation of different internodes in the rice culm may be regulated by different genes, and the loss of function or downregulation of EUI1 , which encodes a P450, CYP714D1 , gave rise to the increase of 1IN [ 24 , 25 , 26 ]. After pyramiding the favorable alleles from the three loci into a single genotype, the 1IN length might increase to 3.08 cm ( Supplementary Table S14 ).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This indicates that this favorable allele could be used to increase the length of the 1IN in breeding programs and, consequently, would be of great value for panicle exertion enhancement. It is supported by previous studies that the elongation of different internodes in the rice culm may be regulated by different genes, and the loss of function or downregulation of EUI1 , which encodes a P450, CYP714D1 , gave rise to the increase of 1IN [ 24 , 25 , 26 ]. After pyramiding the favorable alleles from the three loci into a single genotype, the 1IN length might increase to 3.08 cm ( Supplementary Table S14 ).…”
Section: Discussionmentioning
confidence: 52%
“…For the top first internode, four QTLs were detected on chromosomes 3, 7, 8 and 9, explaining 20.3% of the total phenotypic variation [ 23 ]. Until today, several studies have cloned and elucidated the function of the elongated uppermost internode gene, designated as EUI1, which is characterized by the near doubling 1IN [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, 56 quantitative trait loci (QTLs) controlling PEL have been identified and distributed on 12 chromosomes of rice ( Yamamoto et al., 2001 ; Hittalmani et al., 2002 ; Zhu, 2003 ; Zhu et al., 2006 ; Qiao et al., 2007 ; Xiao et al., 2008 ; Yang et al., 2009 ; Yang et al., 2011 ; Yin et al., 2013 ; Jing et al., 2015 ; Zhao et al., 2015 ; Gao et al., 2016 ; Dang et al., 2017 ). Four genes, EUI2 , EUI1 , SUI1 , and Hox12 , have been cloned to control PEL.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the interaction of genotype by genotype (G × G) and genotype by environment (G × E) contributed to the trait variation (Cho et al, ; Hittalmani et al, ; Zhang et al, ). Correlation analysis also revealed the strong relationship between PL and other agronomic traits, including panicle culm length, plant height, heading stage, secondary branch number and spikelet number per panicle, and these correlated traits are usually mapped synchronously (Dang et al, ; Guo & Hong, ; Huang et al, ; Jang et al, ; Liang, Shang, Lin, Lou, & Zhang, ; Lu et al, ; Miura et al, ; Sun et al, ; Wu et al, ; Yan et al, ; Zhang, Luo, Xu, Zhang, & Xing, ), Genetic dissection for rice plant architecture showed that the PL QTL is co‐localised with either culm length, tiller number or both (Kobayashi et al, ) and finely mapped with the same locus for spikelet number per panicle (Guo & Hong, ; Xie et al, ). However, whether the loci are in tight linkage or genes are in pleiotropy is unclear.…”
Section: Introductionmentioning
confidence: 99%